Prickly Pear or Argan Tree? Agrosilvopastoral Systems of a Mountain Valley in Ait Baamrane (Morocco) Face Changes - Majda Mourou; Antonin Adam; Clothilde Cardon; Mohamed Aderghal; Michel Vaillant; Lhassan Benalayat; Bruno Romagny (Revue de Géographie Alpine)
The Tazrout valley, embedded in the Ait Baamrane area (Moroccan Anti-Atlas), is characterized by agro-ecological conditions hardly favorable to agriculture (arid climate, rugged terrain, poor soils). For a long time, people tackled these environmental challenges through the combined and concerted management of agrosilvopastoral resources and of various spatial dynamics. However climatic disturbances during the 20th century have resulted in the structural transformation of agrarian systems and the destabilization of the social foundations underlying the territory's organization. The widespread planting of prickly pear (cactus) seems to go hand in hand with these changes. According to studies carried out in the region, the cactus has favoured the return of a relative ecological equilibrium; being a sign of resilience. But what about socio-economic benefits? Could the cactuses’ expansion not be a catalyst of the system’s transformation as well as an aggravating factor of social weaknesses? Based on a systemic and geo-historical approach to agrarian structures, this article seeks to understand how successive changes in (i) modes of spatial development and occupation and (ii) public policies have lead today to new vulnerabilities. In order to propose an extension to the trajectory of the territories vulnerability, an alternative scenario to the advancements, seemingly advocated by the State today, is studied.